Recognition of Indigenous Peoples in the Perspective of Legal Pluralism Theory: A Critique of Legal Positivism's Dominance in Indonesia - Gugum Surya Gumilar; Saefullah (Jurnal Kewarganegaraan, 2026)
The recognition of indigenous peoples in the Indonesian legal system has been constitutionally affirmed through Article 18B paragraph (2) and Article 28I paragraph (3) of the 1945 Constitution of the Republic of Indonesia. However, such recognition remains theoretically problematic because indigenous communities and their customary laws are often considered legally valid only after being validated by the state. This article aims to examine the recognition of indigenous peoples from the perspective of legal pluralism, criticize the dominance of state-centered legal positivism, and propose a reconstruction of indigenous recognition based on substantive legal pluralism. This study employs normative legal research using statutory, conceptual, case, and legal-philosophical approaches. The analysis shows that the recognition of indigenous peoples in Indonesia still reflects weak legal pluralism, as customary law has not been fully treated as a normative order equal to state law. The novelty of this article lies in the development of substantive legal pluralism as a legal-theoretical framework to shift indigenous recognition from a formal-administrative model toward a substantive-participatory model. This article argues that customary law should not be reduced to social custom, but should be understood as living law that possesses social validity, is obeyed, and operates within indigenous communities.